Art and nature in the anthropocene : planetary aesthetics - Ballard, Susan, 1969- (New York, NY : Routledge, 2021)
"This book examines how contemporary artists have engaged with histories of nature, geology, and extinction within the context of the changing planet. Susan Ballard describes how artists challenge the categories of animal, mineral and vegetable-turning to a multispecies order of relations that opens up a new vision of what it means to live within the Anthropocene. With a particular focus on artists from Australia and Aotearoa New Zealand this book reveals the emergence of a planetary aesthetics in the work of contemporary artists. The book will be of interest to scholars working in art history, visual culture, narrative nonfiction, digital and media art, and the environmental humanities"--
In the holocene -- Landscapes of the anthropocene -- New taxonomies -- Acceleration -- Moving beyond geology.
OCLC-licensed vendor bibliographic record.
Keywords: Nature in art; Geology in art; Nature (Aesthetics); Art, Modern -- 21st century -- Themes, motives; ART / History / Contemporary (1945-); ART / History / General